Dylan Thomas’s Animal Symbology in Celtic Tradition: The Inner Voice of a Poet - Rodríguez Gómez, Paula María (Miscelánea: A Journal of English and American Studies, 2003)
By means of a mythic journey into the collective unconscious, Dylan Thomas transforms his Welsh cultural values into a symbolic synthesis that explains the poet’s presence in Cosmos· as a link between nature and man. Native Welsh tradition is ever present in the outstanding number of animal symbols that Dylan Thomas enlivens his poetry with. His readers become thus initiated into . the mysteries of his classical concerns about evolution and the nature of man. Animal symbols play an all important role in a system of opposites that Thomas weaves in his poems. This scheme becomes the core of poetic significance as an expression of mythological wisdom, and its symbols represent clues that disentangle the way into inner human truth within the chaos depicted by Thomas’s own Modernist universe.